2016
DOI: 10.1007/s10695-016-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, promoter analysis and expression of the interleukin-6 gene in blunt snout bream, Megalobrama amblycephala

Abstract: Interleukin-6 (IL-6) is one of the most important multifunctional cytokines, playing essential roles in mediating the innate and adaptive immune responses. In this study, il-6 gene and its promoter from blunt snout bream, Megalobrama amblycephala, were characterized, and its expression at the transcript level in healthy fish and after bacterial infection was determined by quantitative real-time PCR. The results showed that the M. amblycephala il-6 (Mamil-6) cDNA had an ORF of 699 bp, encoding 232 amino acids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The comparison of functional cis-regulatory elements from human and tsIL-6 promoter regions is shown in Fig. 3B ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of functional cis-regulatory elements from human and tsIL-6 promoter regions is shown in Fig. 3B ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our lab indicated that some immune-related genes are activated at an early stage of A. hydrophila infection in M. amblycephala [31,32,33,34,35]. Therefore, three small RNA libraries were analyzed from M. amblycephala liver at 0 (non-infection), 4, and 24 h post infection (poi) using the Illumina Hiseq 2000 sequencing platform.…”
Section: Resultsmentioning
confidence: 99%
“…The il-6 gene has been identified in several teleost, such as zebrafish (Danio rerio, Hamilton 1822) [30], fugu (Takifugu rubripes, Temminck & Schlegel 1850) [31], Paralichthys olivaceus (Temminck & Schlegel, 1846) [32], Sparus aurata (Linnaeus, 1758) [33], Larimichthys crocea (Richardson, 1846) [34], rainbow trout (Oncorhynchus mykiss, Walbaum 1792) [35], and blunt snout bream (Megalobrama amblycephala, Yi Bolu 1955) [36]. In teleost, IL-6 has been proved to play vital roles in the immune response, inducing the expression of hamp and regulating cytokines genes (il-1β and il-6) and socs1-3 [33,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The blunt snout bream il-6 gene could be strongly induced in Aeromonas hydrophila (Kluyver & Van Niel, 1936) in many tissues, indicating that il-6 plays an active role in the defense against pathogens [36,42]. IL-6 amino acid sequence in blunt snout bream (maIL-6) shares 91% identity with that of grass carp (Ctenopharyngodon idellus, Cuvier et Valenciennes 1844) (ciIL-6), but only 23-30% identity with those of mammals, birds, and amphibians [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation